Preliminary experiments on hohlraum-driven double-shell implosion at the ShenGuang-III laser facility. (4th June 2018) - Yan, Ji; Zhang, Xing; Li, Jiwei; Dai, Zhensheng; Chen, Bolun; Jing, Longfei; Chen, Zhongjing; Huang, Tianxuan; Jiang, Wei; Yu, Bo; Pu, Yudong; Song, Zifeng; et al.
Abstract: Double-shell implosion is proposed as a non-cryogenic target design for ignition, offering a robust implosion platform for inertial confinement fusion research. Hohlraum-driven double-shell implosions have been performed at the ShenGuang-III laser facility; a vacuum hohlraum with a high CCR value was employed. With 96kJ laser energy in a squared temporal profile, the implosion neutron yield was close to 10 10, and the YOC1D was about 27%. A fuel areal density of 14 mg cm −2 was inferred from the measured yield ratio of secondary and primary neutrons. The implosion trajectory was diagnosed via the 4.75 keV x-ray backlight. The measured implosion velocity and hot-spot x-ray emission history indicate a predictable hydrodynamic process in the double-shell implosion. Two crucial factors which might detrimentally affect implosion performance are the implosion symmetry and pusher–gas mix. The loss of four driven laser beams in the backlight shot caused the YOC1D to decrease to 5% and fuel areal density to decrease to 4 mg cm −2 . In future, optimization of the implosion symmetry and the capsule fabrication will be implemented to improve the double-shell implosion performance.